Effect of spraying zinc , tryptophan and thiamin on growth and yield of grapevine cv. "khalili" - Abbas, Al-Abbas M.; Hasan, Ahmed M. (Journal of Kerbala for Agricultural Sciences, 2018)
This research was conducted in aprivate orchard located in Bermanah/Babylon government during the growing season 2017 to study the effect of spraying Zinc, Thiamine and Tryptophan on the growth and yield of " Khalili " grapevine planted in parallel lines with dimensions ( 2 * 2)m growing on wired vine pergola , 45 vines possess the same force were selected, 45 buds were left spread upon 15 spur/vine , every spur contain 3 buds. The experiment included two factors the first was Foliar applied Zinc ( Disper Zn Sinergy) at three concentrations (0, 0.5 , 1) g.l-1, the second factor was spraying with Thiamine ( 50 , 100 ) mg.l-1 ,Tryptophan ( 50 , 100 ) mg.l-1 and With out Spraying . first date was in 15/ 4 /2017 when flowering clusters appeared before bloming and the second date was after 20 days of first foliar application on 4/ 5/ 2017 .The factorial experiment used was a Split-Plot design (5 * 3) and was done in randomize complete block design (RCBD)with three replicates. The results could be Summarized as follows: The Spraying of Zinc at (0.5g.l-1) concentration leading to the increment in the size of 100 grapes and the percentage of IAA hormone in the leaves,while was for the spray of zinc at a(1g.l-1)concentration a significant influence in the increment of chlorophyll content in the leaves.Thiamine spraying at (100mg.L-1) concentration having an effect in the increment of weight and size of 100 grapes and also increase the fructose percentage in the grapes,while spraying of thiamine at (50 mg.L-1)concentration was led to a significant increment in the leaf area and IAA level in the leaves.while was for the overlap between treatments a significant effect in all qualities except leaf area, where gave the(Z1T4) interference the highest value for the weight and size of the 100 grapes reached( 383g ,323.7cm3 )respectively .while (Z0T0) interference gave the lowest size of 100 grape was( 210cm3) ,the lowest value for the weight of 100grapes was (254.3g) at the (Z1T0).The effect of overlapping on the relative content of chlorophyll (Z2T2)interference gave the highest relative content of chlorophyll reached (42.37 SPAD),while the lowest relative content of chlorophyll was (33.47 SPAD) for (Z0T0) interference .The effect of overlapping on the content of grapes from fructose sugar, (Z0T4) interference gave the highest content of fructose reached (12.31g.100L-1) and the (Z0T0) interference gave the lowest content of fructose reached (9.30g.100L-1).while was for the (Z1T3)overlap the highest effect in increasing the content of leaves from indol hormone reached (74.9 µg.g-1),and the (Z0T0) overlap gave the lowest content of the hormone was( 13.7µg.g-1)